Struktur Kepribadian Tokoh Utama dalam Cerpen Kalaupun Mati Aku Mau dalam Dekapan Ibu - Febriani, Dwi; Zahir, Khairunnisa Kamila; Kurniawan, Eva Dwi (HUMANUS : Jurnal Sosiohumaniora Nusantara, 2023)
This research aims to explain the personality structure of the main character in the short story entitled "Even If I Die, I Want to be In My Mother's Arms" which comes from a collection of short stories by Isbedy Stiawan ZS entitled I’m a Female You’re a Woman. This research is a qualitative descriptive study based on Sigmund Freud's psychoanalytic theory. Data was obtained using reading and note-taking techniques. The method used uses a literary psychology approach. The results obtained show that the main character (Aku) in the short story “If I Die, I Want to be In My Mother's Arms" has an id, ego, and superego. The main character (Aku) tends to be controlled by the id, this can be seen from the short story quotes which directly and indirectly describe the behavior of my character as a robber who kills his victims. A dominant id can occur because the individual's ego cannot take over the id and superego optimally, resulting in an imbalance in the character's personality structure. Psychologically healthy individuals tend to be dominated by ego. So it can be said that my character is psychologically unhealthy.